Answers

2014-06-14T14:15:38+05:30
I) x + y =3.3 and (0.6/3x-2y)-2y= -1 
=>x=3.3-y------------(1) and 0.6/{3(3.3-y)}-2y=-1
=>0.6/(9.9-3y-2y)=-1----------------From (1)
=>0.6/(9.9-5y)=-1  =>0.6=-1(9.9-5y)  =>0.6=-9.9+5y  =>10.5=5y  =>y=2.1
ii)1/2x-1/y=-1 and 1/x+1/2y=8
=>y-2x/2xy=-1  =>y-2x=-2xy  =>y+2xy=2x =>y(1+2x)=2x  =>y=2x/(1+2x)
Therefore,1/x+1/2y=8  =>1/x+1/2[2x/(1+2x)]=8  =>1/x+2x/(2+4x)=8  =>2+4x+2x
²/[x(2+4x)]=8
=>2x²+4x+2/(2x+4x²)=8  =>2x²+4x+2=8(2x+4x²)  =>2x²+4x+2=16x+32x²  
=>32x²-2x²+16x-4x-2=0  =>30x²+12x-2=0  =>2(15x²+6x-1)=0  =>15x²+6x-1=0  =>...........question is may be wrong.
iii) 43x+67y=- 24 and 67x+ 43y= 24
=>
1 5 1